(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2024)
In this work, we study the Greco-Iberian inscription on the lead sheet that appeared folded at the beginning of 2018 in the Illeta dels Banyets site. The sheet comes from a superficial stratum, but probably belongs to the final moment of the first phase of the site from the mid-4th century BC. The plate appears complete, and the documented texts are three, one on each side occupying the first two lines and a third with unclear reading in the lower right corner of the exterior side. It does not seem that the different texts form a unit, but rather it could be a triple reuse of the support. This behaviour could fit with what is expected on a label, where the active text would be the one that occupies the upper part of the visible face once the fixed sheet is placed on the product. The first text on the inside contains an anthroponym, ildurkon or ildurbon, and the second line contains a metrological expression, oś<(<), perhaps the price, probably with the abbreviated indications of otar (= 10 or 12 ś) and śalir, representing the drachma, and with < indicating a fraction, perhaps the one corresponding to the obols, if the symbol absent in this expression, X, represented the hemidracma. The text on the outer face contains an anthroponym, ka+belauŕ, and in the second line it contains the element nai, equivalent to the northeastern Iberian ḿi and which is characteristic of the speaking inscriptions of property.